1983
DOI: 10.1007/bf01852288
|View full text |Cite
|
Sign up to set email alerts
|

Mikroangiographische Untersuchungen verschiedener menschlicher Tumoren nach Transplantation auf thymusaplastische Nacktmäuse

Abstract: Ten different human tumors (two soft tissue sarcomas, seven adenocarcinomas of the colon and stomach and, one squamous cell carcinoma of the lung) were implanted s.c. in thymus-aplastic mice and retransplanted over several generations. In 40 animals, the tumors were studied by microangiography and microscopy and classified according to angiographic tumor criteria. Tumor transplants always revealed similar angiographic patterns. The microscopic results presented a good correlation with the roentgenologic findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
1999
1999

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Studies on human tumour xenografts in nude mice have shown that a similar histology is not necessarily correlated to a comparable vascular pattern (Solesvik et al . 1982, Kraus et al . 1983) .…”
Section: Tumour Vascular Morphologymentioning
confidence: 99%
“…Studies on human tumour xenografts in nude mice have shown that a similar histology is not necessarily correlated to a comparable vascular pattern (Solesvik et al . 1982, Kraus et al . 1983) .…”
Section: Tumour Vascular Morphologymentioning
confidence: 99%